A Quantitative Assessment of Price and Income Effects on Cooking Oil Demand - Fahrial Fahrial; Alfando Syahputra Ginting (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Cooking oil is a vital household commodity in Indonesia, yet its demand faces challenges from rising prices, limited availability, varying income levels, and shifting market preferences. These factors influence consumption patterns, particularly in rural areas where economic and market conditions differ from urban settings. This study aims to examine household characteristics, explore the nature of cooking oil demand, and identify factors influencing this demand in Pematang Tebih Village, Ujungbatu Subdistrict, Rokan Hulu Regency, Riau Province. Using a survey method, data were collected from 86 households across five hamlets, selected via simple random sampling. Descriptive analysis outlined household profiles and consumption patterns, while multiple linear regression analysis determined key influencing factors. Findings reveal that households, with an average age of 32 to 36 years and three family members, earn approximately 5,701,163 Indonesian Rupiah monthly. Most prefer packaged cooking oil priced between 15,000 and 17,000 Indonesian Rupiah per liter, with Minyakita as the dominant brand, consuming up to 4 liters monthly. Key factors affecting demand include prices of palm, bulk, and coconut cooking oils, wheat flour price, population income, and population size, explaining 85.1 percent of demand variation. In conclusion, these insights highlight the need for stable pricing and supply strategies to enhance affordability and food security in rural communities.